Pelatihan Bahasa Inggris bagi Calon Perawat di Maluku di Masa Pandemi Covid-19 - Dwi Yulianto Nugroho (Universitas Lancang Kuning, 2022)
Maluku Province has tourism attraction which can attract international visitors to visit Maluku. However, those tourists in Maluku might get sick and be treated in hospital. In this case, nurses play an important role for the patient's recovery. They must treat all patients according to their responsibilities, regardless of differences in ethnicity, religion or origin of the patient. One of the trainings they need is English language training to prepare them to handle foreign patients who do not speak Indonesian and only understand English. For this reason, this Community Service (PkM) activity is proposed to accommodate the needs of learning English for prospective nurses in Maluku. Learning activities were carried out in a period of 10 sessions and approximately there were 3-5 participants per meeting joined the training. The learning approach used was the flipped-learning approach which has positive impacts on the participants. The participants felt more confident to speak English and English skills in nursing context increased after completing the program. However, there were some challenges faced by the participants, namely related to their English language skills and inadequate quality of the internet network in the area where the participants joined the program. Recommendations for future English trainers are explained in this paper. Similar future programs could implement teaching and learning method and approach by considering participants’ internet connection quality. In addition, training on General English should be carried out first before training on English for Specific Pusposes is implemented.